GENERALIZED STABILITY OF AN ADDITIVE-QUADRATIC FUNCTIONAL EQUATION IN VARIOUS SPACES - ALSHYBANI, SHAYMAA (Al-Qadisiyah Journal of Pure Science, 2019)
ABSTRACT. In this paper, using the direct and fixed point methods, we have established the generalized Hyers-Ulam stability of the following additive-quadratic functional equation in non-Archimedean and intuitionistic random normed spaces. AMS 2010 Subject Classification: 39B82, 39B52, 46S40. Keywords. generalized Hyers-Ulam stability; additive mapping; quadratic mapping; non-Archimedean random normed spaces; intuitionistic random normed spaces; fixed point.